1998
DOI: 10.4315/0362-028x-61.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Enterotoxigenic Clostridium perfringens in Spices Used in Mexico by Dot Blotting Using a DNA Probe

Abstract: Several reports on the microbiology of spices and herbs indicate the presence of Clostridium perfringens, a spore-forming foodborne pathogen responsible for gastrointestinal disease. In the present study, a total of 380 samples of spices and herbs (cumin seed, black pepper, oregano, garlic powder, and bay leaves) widely used in Mexico were analyzed for the presence of C. perfringens, and the enterotoxigenicity of the isolates was determined by a dot-blot technique using an enterotoxin digoxigenin-labeled DNA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…perfringens is classified into five types (A, B, C, D, and E) based on the production of four major toxins (alpha, beta, epsilon, and iota toxins) and hydrolytic enzymes including lecithinase, hemolysins, hyaluronidase, collagenase, DNAse, and amylase (Brynestad and Granum 2002). Molecular epidemiological surveys suggest that only a small fraction (1% to 5%) of all C. perfringens isolates, mainly belonging to type A, are capable of producing an enterotoxin responsible for food poisoning (Brynestad and Granum 2002;Rodriguez-Romo et al 1988). In addition, it has also been reported that most, and perhaps all, C. perfringens type E that have been isolated carry silent, defective cpe (C. perfringens enterotoxin gene) sequences (Billington et al 1998).…”
Section: The Organismmentioning
confidence: 99%
“…perfringens is classified into five types (A, B, C, D, and E) based on the production of four major toxins (alpha, beta, epsilon, and iota toxins) and hydrolytic enzymes including lecithinase, hemolysins, hyaluronidase, collagenase, DNAse, and amylase (Brynestad and Granum 2002). Molecular epidemiological surveys suggest that only a small fraction (1% to 5%) of all C. perfringens isolates, mainly belonging to type A, are capable of producing an enterotoxin responsible for food poisoning (Brynestad and Granum 2002;Rodriguez-Romo et al 1988). In addition, it has also been reported that most, and perhaps all, C. perfringens type E that have been isolated carry silent, defective cpe (C. perfringens enterotoxin gene) sequences (Billington et al 1998).…”
Section: The Organismmentioning
confidence: 99%
“…However, many di#erent spices are contained in curry roux, and C. perfringens has been found in turmeric, coriander, fenugreek and mustard 8) . Rodrı ÿ guez-Romo et al 7) detected the enterotoxin gene in several Clostridium perfringens strains isolated from spices such garlic ῎: Clostridium species other than Clostridium perfringens were detected using the indicated methods. g ῐ: Clostrdium perfringens was detected using the indicated methods.…”
Section: Occurrence Of Clostridia In Commercially Available Curry Roumentioning
confidence: 99%
“…In Japan, outbreaks of food poisoning caused by C. perfringens are often traced back to curry, and since curry usually contains animal meat, most C. perfringens strains isolated from curry are likely to be derived from animal meat. However, Rodrı ÿ guez-Romo et al 7) detected the enterotoxin gene in some strains of C. perfringens isolated from spices. In this study, the occurrence of clostridia in samples of commercially available curry roux was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…to detect B. cereus from traditional Indian foods [334] and for enterotoxic B. cereus detection [261]. DNA hybridization has also been used to identify enterotoxic C. perfringens strains [85,411] and to detect enterotoxic C. perfringens from Mexican spices and herbs [343] and from the feces of Mexican subjects [418].…”
Section: Hybridizationmentioning
confidence: 99%